2012
DOI: 10.1017/s1062798711000627
|View full text |Cite
|
Sign up to set email alerts
|

Strangers on the Move: Ethnic Entrepreneurs as Urban Change Actors

Abstract: Abstract:This paper aims to examine the critical conditions for success and failure for the new generation of ethnic entrepreneurs in the creative industries in modern Dutch urban areas, in terms of their entrepreneurial behaviour with a particular focus on their personal and business characteristics and their motivation and driving forces, which all determine their entrepreneurship and their business performance. An empirical application is presented, in which the results from an in-depth interview study of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…The socio-economic profile of the current migrant volumes is often rather different from that of the host population in terms of demographic, cultural and entrepreneurial attributes. Worldwide, migrant settlement tends to be concentrated in specific geographical magnets (or attraction poles), in particular in the metropolitan agglomerations of the developed world (Longhi et al 2010;Kourtit, Nijkamp 2012). It is of course important to know whether foreign migrants have a positive or negative long-range impact on the local, regional or national economy; their -in-groups and between-groups -diversity may lead to vast differences in the economic migration impact.…”
Section: Setting the Scene: The Homo Mobilismentioning
confidence: 99%
See 3 more Smart Citations
“…The socio-economic profile of the current migrant volumes is often rather different from that of the host population in terms of demographic, cultural and entrepreneurial attributes. Worldwide, migrant settlement tends to be concentrated in specific geographical magnets (or attraction poles), in particular in the metropolitan agglomerations of the developed world (Longhi et al 2010;Kourtit, Nijkamp 2012). It is of course important to know whether foreign migrants have a positive or negative long-range impact on the local, regional or national economy; their -in-groups and between-groups -diversity may lead to vast differences in the economic migration impact.…”
Section: Setting the Scene: The Homo Mobilismentioning
confidence: 99%
“…This 'new entrepreneurship' -distinct from 'normal' entrepreneurship -started originally by an orientation towards migrant products and services ('ethnic goods'), migrant market customers, or indigenous or traditional migrant business growth strategies (Choenni 1997;Masurel et al 2002Rusinovic 2006;Sahin et al 2007;Kourtit, Nijkamp 2012). A wealth of recent research has addressed opportunities for and barriers to successful migrant entrepreneurship.…”
Section: Migrant Entrepreneurship: Diversity In Motivesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy, that -most of these firms have started in a rather informal and flexible way, but -especially in the stage of second-generation migrants -they have been upscaled to modern R&D-oriented firms ('break-out approach') (Kourtit and Nijkamp 2011b). Recent research (Sahin et al 2010(Sahin et al , 2012Kourtit and Nijkamp 2012) has shown that the second generation of ethnic entrepreneurs tends to be well-educated, and better integrated in the host 4 community, where this community is mostly also the country of birth of this new generation.…”
Section: Migrant Entrepreneurshipmentioning
confidence: 99%